A DESCRIPTIVE STUDY ON TEACHING VOCABULARY TO THE FOURTH YEAR STUDENTS OF MI AL FALAH BAKI SUKOHARJO IN 2006/2007 ACADEMIC YEAR - PAMUNGKASARI , NOVALITA (2007)
The objectives of this study are to describe the technique in teaching vocabulary, to describe the students' difficulties in learning vocabulary and to describe the strategies to solve the students' difficulties in learning vocabulary at the Fourth Year Students of MI AL FALAH BAKI SUKOHARJO. The writer focuses on the English Vocabulary teaching process. The data are taken from direct observation in the classroom, interview with the English teacher and collecting documentation. The study shows that: 1) The teacher uses some techniques in teaching vocabulary. They are lecturing, translating, drawing, and using pictures, 2) There are difficulties faced by the learners when they learn vocabulary. They are the pronunciation difficulties and the spelling difficulties, 3) The teacher uses strategies to solve the students' difficulties in learning vocabulary. Those are giving an exercise with memorizing or pronouncing new words, giving more dictation drill in English, giving an assignment to look for new words, and giving a suggestion to always ask if they find some difficulties.